Dampak Partisipasi Wanita Dan Faktor Demografi Dalam Pengelolaan Hutan Kemasyarakatan (Hkm) Terhadap Pendapatan Keluarga Di Kabupaten Lampung Barat - Rio Yudischa; Christine Wulandari; Rudi Hilmanto (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Community Forest (HKM) is a community development schemes through strengthening factors of production of non-timber forest products in the form of access to forest lands, protected primary forest. It is not yet known impact of women's participation in community forest management on family income in the village Tribudi Syukur and Tribudi Makmur. To the end, the research conducted in order to know the impact of demographic and participation of women in community forest management on family income in the village Tribudi Syukur and Tribudi Makmur, Kebun Tebu sub district, West Lampung, Lampung province. This research was conducted in the Community Forest, at Village Tribudi Syukur and Tribudi Makmur. Data retrieved using the method of data collection simple random sampling. Analysis of data used linear models was assisted using Minitab 16 software for parameter optimization. The results showed that the factor land size and income of women farmers with a significant effect on the income of women's participation in community forest management. Meanwhile, the chief factor of the family, the woman's age, the age of the male, female participation rates, female education, male education, number of dependents, and the distance to the arable land were not significantly associated with women's participation in the management of the community forest income. Keywords: community forest, women's participation, income